Supporting Aspect Oriented Requirements Engineering for Large Documents - Zambrano Polo y La Borda, Arturo Federico (2011)
Performing Aspect Oriented Requirements Engineering for large documents is a hard task. This is due to the lack of tools that support demarcation and tracking of crosscutting concerns for requirements documents. In this paper we present the requirements and current implementation status of AORE Assistant, a tool aimed at helping the engineer to manage large documents with multiple crosscutting concerns. Such tool should improve software development cycle by easing the location of crosscutting concerns in the documents and helping to avoid problems derived from neglected concerns interactions.